2020
DOI: 10.5223/pghn.2020.23.3.276
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram for Predicting Non-Alcoholic Fatty Liver Disease in Obese Children

Abstract: Purpose: Non-alcoholic fatty liver disease (NAFLD) ranges in severity from simple steatosis to steatohepatitis. Early detection of NAFLD is important for preventing the disease from progressing to become an irreversible end-stage liver disease. We developed a nomogram that allows for non-invasive screening for NAFLD in obese children. Methods: Anthropometric and laboratory data of 180 patients from our pediatric obesity clinic were collected. Diagnoses of NAFLD were based on abdominal ultrasonographic findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Nomograms are widely used as a user-friendly decision-making tool in precision medicine. In a similar manner, Kim et al used γ-glutamyl transpeptidase, homeostatic model assessment of insulin resistance, ALT, uric acid, and TG as the predictors built a nomogram that can be performed to detect for NAFLD in obese children ( 15 ). Earlier studies have shown that the presence of type 2 diabetes, obesity and age are associated with NAFLD and advanced fibrosis ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nomograms are widely used as a user-friendly decision-making tool in precision medicine. In a similar manner, Kim et al used γ-glutamyl transpeptidase, homeostatic model assessment of insulin resistance, ALT, uric acid, and TG as the predictors built a nomogram that can be performed to detect for NAFLD in obese children ( 15 ). Earlier studies have shown that the presence of type 2 diabetes, obesity and age are associated with NAFLD and advanced fibrosis ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alanine aminotransferase is one of the main liver function tests used to screen for hepatocellular damage and liver dysfunction ( 15 , 21 ). Many studies have showed that ALT was an independent predictor of NAFLD ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations